Analysis of the Children’s Playground with Blue Open Space Concept in Bajau Ethnic Settlement Rampa Lama Kotabaru - Leonard; Siwi, Samsu Hendra; Fatimah, Titin (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2024)
The Rampa Lama Village settlement is a settlement located in a coastal area at the ebb and flow of sea water. This settlement is in the province of South Kalimantan and is located to the north of Kotabaru Regency. The population of Rampa Lama Village is 6,000 people with children aged 6-12 years old who received elementary school education totaled 364 children consisting of 181 boys and 183 girls. This has become a phenomenon regarding the limited children's playground space and its facilities that are safe, comfortable and have safety aspects for the users, in this case children when children play, the Rampa Lama Village settlement is a densely populated area with Public Open Space that can be used as a playground for children in the surrounding area. Public open space for the childrens Rampa Lama need open space blue concept because they are representing fisherman community. The purpose of this research is to analysis public open space for children in coastal areas by implementing a blue concept open space according to the child's character. A study uses a qualitative inductive method with a phenomenological approach. The results of the research were in the form of recommendations for the coastal area of Rampa Lama Village with the existing ethnic character of the Bajau tribe with observations that have been made where the character of the children's play space in the area is Blue Open playground and its application to Child Friendly Playground.